Analysis Of Gerontic Nursing Care for Mrs. T With Hypertension Through the Application of Isometric Handgrip Exercise Therapy in The Bougenville Room Of The Satpel Griya Lansia Garut - Sopia Fauziah, Mala; Puspita, Tantri (Nursing Case Insight Journal, 2025)
Hypertension or high blood pressure is a disease of the heart and blood vessels characterized by increased blood pressure. Factors that influence the incidence of hypertension include genetic, racial, regional, socio-cultural and unhealthy lifestyle. This study aims to determine the analysis of nursing care with hypertension through the application of isometric handgrip exercise therapy in the Griya Lansia Garut service unit. The research method used in this study is descriptive qualitative in the form of a case study by conducting nursing care for the elderly which includes assessment, nursing diagnosis, intervention, implementation, and evaluation of nursing carried out on March 3-9, 2025. Based on the results of the assessment, diagnosis, intervention, implementation and evaluation carried out by the researcher, 4 nursing problems were found, namely impaired physical mobility, anxiety, knowledge deficit and risk of falling. Researchers planned mobilization support by implementing Isometric Handgrip Exercise therapy based on Evidence-Based Practice, which aims to lower blood pressure and increase muscle strength. Nursing care was provided for 5 days, including assessment, diagnosis, intervention, implementation, and evaluation. Results showed a decrease in blood pressure from 170/97 mmHg to 154/80 mmHg and an improvement in muscle strength from scale 4 to 5 after the intervention. The study concluded that isometric handgrip exercise therapy is effective in lowering blood pressure and increasing muscle strength in hypertensive elderly patients. Further quantitative research is recommended to examine the long-term effects of this intervention